Principles of Oocyte and Embryo Donation - Sauer, Mark V.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The versatility of oocyte and embryo donation has proven to be extremely valuable to both patients and doctors engaged in reproductive medicine. Originally thought to be applicable only to a rather small subset of infertile women, today busy practices commonly recommend the procedure and it is estimated that nearly all of the 400 or more IVF programs in the United States provide these services. Oocyte and embryo donation has established itself as a mainstay procedure within assisted reproductive care, and the breadth, depth and complexity of practice is deserving of focused attention. Much has changed within the field of oocyte and embryo donation since the publication of the first edition of Principles of Oocyte and Embryo Donation in 1998, thus the need for a completely updated and more expansive text. The second edition of this book provides an overview of the major issues affecting men and women engaged in the practice of oocyte and embryo donation.  A primary emphasis has been placed on defining the standards of practice that have evolved over the past 30 years, clearly stating the outcomes expected from adhering to these established protocols.  Details of both the basic science and the clinical medicine are presented together and attention is also focused on the non-reproductive aspects inherent to this unique method of assisted reproduction that involves opinions from lawyers, ethicists, mental health care professionals and theologians.  Oocyte and embryo donation requires a working knowledge of the medicine, the law and the ethics that underlies its foundation. This book is intended to serve as a complete and comprehensive reference for all health care professionals that provide services related to egg donation, reproductive endocrinologists, obstetrician- gynecologists, and fellows and residents entering the fertility field.
Part I. PRELIMINARY CONSIDERATIONS FOR PATIENTS AND CLINICIANS -- History of the Technique and its Importance to Understanding Modern Methodology -- Indications for Egg and Embryo Donation -- Success and Anticipated Pregnancy Outcomes for Oocyte and Embryo Donation -- Selecting and Screening Donors -- Selecting and Screening Recipients: Diminished Ovarian Reserve and Premature Ovarian Failure -- Chapter 6 – Selecting and Screening Recipients: Advanced Reproductive Age -- Genetic Aspects of Donor Selection -- Part II. PRACTICAL ASPECTS OF CLINICAL CARE -- Sychronization of Donors and Recipients: Practical Aspects of Clinical Surveillance -- Preparing the Endometrium to Maximize Success: The Dynamic of Artificial Cycles -- Blastocyst versus Cleavage Stage Embryo Transfer: Maximizing Success Rates -- Strategies to Minimize Multiple Births in Recipients of Egg Donation -- What is the Outcome and Fate of Frozen Supernumerary Embryos Resulting from Egg Donation? -- Prenatal Considerations after Oocyte Donation -- Defining, Understanding and Managing the Complex Psychological Aspects of Third Party Reproduction -- Disclosure Decisions Among Known and Anonymous Egg Donor Recipients -- Risk and Complications Associated with Egg Donation -- Part III. OFFICE PRACTICE MANAGEMENT -- The Role of the Donor Oocyte Nurse Coordinator -- The Finances of Egg Donation -- Donor/Recipient Insurance Coverage: Protecting Against Unexpected Liability -- Part IV. NEW FRONTIERS IN EGG AND EMBRYO DONATION -- Egg and Embryo Banking: Essential Elements for Maintaining High Rates of Success -- Gestational Carriers and Surrogacy -- Assisted Reproduction in Same Sex Couples -- Immunologic and Clinical Consequences of Oocyte Donation Pregnancies -- Part V. LEGAL AND REGULATORY ISSUES -- FDA Regulatory Approach to Reproductive Tissues -- Essential Elements of Informed Consent in Egg Donation and Surrogacy -- Statutory and Case Law Governing the Practice of Third Party Reproduction -- Part VI. CULTURE, RELIGION AND ETHICS -- Health Equity and Access to Oocyte Donation -- Religious Views: The Impact of Traditional Theological Opinion on the Practice of Third-Party Reproduction -- Ethics of Egg and Embryo Donation -- Ethical Issues: Addressing the Sensational Cases and Analyzing the Clinical Practice.
Keywords: Reproductive medicine; Endocrinology .; Gynecology .; Obstetrics; Reproductive Medicine; Endocrinology; Gynecology; Obstetrics/Perinatology/Midwifery.